Hydroclimatic impacts of the abrupt cooling event 8200 years ago in the western Indo-Pacific Warm Pool - Dixit, Yama (2025)
The most prominent abrupt climate event during the Holocene, the ‘8.2 ka event’, was characterized by severe cooling at high northern latitudes causing diverse hydroclimate shifts globally. A precise understanding of the hydroclimate response of the Indo-Pacific Warm Pool (IPWP) region to the 8.2 ka cooling, remains elusive. Here we present sub-centennial stable carbon isotope record on benthic foraminifera Asterorotalia pulchella and X-ray fluorescence elemental data of a marine sediment core from the Kallang River Basin, Singapore. We show that the rainfall in the western IPWP weakened for ~200 years at ~8.15 ± 0.03 ka BP, consistent with other regional and Southern Hemispheric records, however there is a lag of ~100 years from the North Atlantic cooling. A north-south signal propagation from the North Atlantic possibly via oceanic along with atmospheric routes operating on centennial scales led to southward location of Intertropical convergence zone causing droughts in Southeast Asia.